Impact of Authentic Leadership on Transformative Learning of Higher Education Institution (HEI) Employees, Interceded by the Moral Values of Employees. - Mohammad Ali Haider Chauhan; Dr. Naveed Yazdani (Journal of Management Practices, Humanities and Social Sciences, 2022)
This empirical study explains the correlation between Authentic Leadership (AL) and Transformative Learning (TL). In the recent history of corporations and the business world, corporate scandals have erupted, which have questioned the authenticity of the leaders. This empirical study undertaken by the researcher explores the construct of AL and its impact on the TL of followers. The Moral Values (MV) of the followers act as a mediator in this relationship, and the study finds that AL directly impacts TL. The study has its limitations as it was conducted in higher education institutes employees. It is recommended that this study be undertaken with more variables, mediators, and moderators to understand this extraordinary impact of AL on TL and enhance the two fields. This empirical study explains the correlation between AL and TL. Taken all together, based on empirical evidence, this research identifies that AL qualities perform a significant role in increasing TL. In addition, those employees have high MV their TL is high as compared to others. The study explores relational support through two theories, social learning theory, and social cognitive theory, that provide bases to generate arguments.